2001
DOI: 10.1046/j.1365-313x.2001.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Single ribosomal transcription units are linear, compacted Christmas trees in plant nucleoli

Abstract: SummaryThe rDNA transcription units are enormous macromolecular structures located in the nucleolus and containing 50±100 RNA polymerases together with the nascent pre-rRNA attached to the rDNA. It has not previously been possible to visualize nucleolar transcription units directly in intact nucleoli, although highly spread preparations in the electron microscope have been imaged as`Christmas trees' 2±3 mm long. Here we determine the relative conformation of individual transcription units in Pisum sativum plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
(60 reference statements)
4
40
0
Order By: Relevance
“…AtNUC-L1 is localized in the nucleolus in the DFC surrounding FC at the site of rRNA transcription (which occurs in the border zone between FC and DFC; Gonzalez-Melendi et al, 2001, and references therein); we also demonstrate that AtNUC-L1 disruption has a major effect on nucleolus structure. We have observed that the nucleolus is completely disorganized in the Atnuc-L1 plant, reminiscent of the ultrastructural changes observed in the yeast nucleolus of gar2 (Leger-Silvestre et al, 1997).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…AtNUC-L1 is localized in the nucleolus in the DFC surrounding FC at the site of rRNA transcription (which occurs in the border zone between FC and DFC; Gonzalez-Melendi et al, 2001, and references therein); we also demonstrate that AtNUC-L1 disruption has a major effect on nucleolus structure. We have observed that the nucleolus is completely disorganized in the Atnuc-L1 plant, reminiscent of the ultrastructural changes observed in the yeast nucleolus of gar2 (Leger-Silvestre et al, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…Occasionally, depending on cell type and stage, other structures such as vacuoles can also be observed in plant nucleolus (Gonzalez-Melendi et al, 2001). It has been accepted for some time that ribosome biosynthesis occurs in a vectorial pattern within the nucleolus.…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana, which has $800 rRNA genes per diploid cell, $50% of the units are estimated to be active. Electron microscopy observations indicate that there are $300 units active in pea nucleoli (Gonzalez-Melendi et al 2001). By extension, nearly all units of T. dubius origin might be active in the 2603-33 individual.…”
Section: Discussionmentioning
confidence: 91%
“…In Pisum sativum, only about 5% of the units are transcribed (González-Melendi et al 2001). Thus, a small fraction of rRNA genes from only one locus seems to be sufficient to supply all the ribosomal machinery of a cell.…”
Section: Resultsmentioning
confidence: 99%